Respuesta :
[tex]f''(\theta)=\sin\theta+\cos\theta[/tex]
[tex]f'(\theta)=\displaystyle\int f''(\theta)\,\mathrm d\theta=\int(\sin\theta+\cos\theta)\,\mathrm d\theta[/tex]
[tex]f'(\theta)=-\cos\theta+\sin\theta+C_1[/tex]
Given that [tex]f'(0)=4[/tex], you have
[tex]4=-\cos0+\sin0+C_1\implies C_1=5[/tex]
[tex]f(\theta)=\displaystyle\int f'(\theta)\,\mathrm d\theta=\int(-\cos\theta+\sin\theta+5)\,\mathrm d\theta[/tex]
[tex]f(\theta)=-\sin\theta-\cos\theta+5\theta+C_2[/tex]
and given that [tex]f(0)=3[/tex], you get
[tex]3=-\sin0-\cos0+5(0)+C_2\implies C_2=4[/tex]
and so
[tex]f(\theta)=-\sin\theta-\cos\theta+5\theta+4[/tex]
[tex]f'(\theta)=\displaystyle\int f''(\theta)\,\mathrm d\theta=\int(\sin\theta+\cos\theta)\,\mathrm d\theta[/tex]
[tex]f'(\theta)=-\cos\theta+\sin\theta+C_1[/tex]
Given that [tex]f'(0)=4[/tex], you have
[tex]4=-\cos0+\sin0+C_1\implies C_1=5[/tex]
[tex]f(\theta)=\displaystyle\int f'(\theta)\,\mathrm d\theta=\int(-\cos\theta+\sin\theta+5)\,\mathrm d\theta[/tex]
[tex]f(\theta)=-\sin\theta-\cos\theta+5\theta+C_2[/tex]
and given that [tex]f(0)=3[/tex], you get
[tex]3=-\sin0-\cos0+5(0)+C_2\implies C_2=4[/tex]
and so
[tex]f(\theta)=-\sin\theta-\cos\theta+5\theta+4[/tex]
[tex]\bf f''(\theta)=sin(\theta)+cos(\theta)\qquad thus
\\\\\\
\displaystyle \int [sin(\theta)+cos(\theta)]d\theta\implies -cos(\theta)+sin(\theta)+C =\underline{f'(\theta)}
\\\\\\
\textit{now, we know \underline{f'(0)}=4}\implies =-cos(0)+sin(0)+C=\underline{4}
\\\\\\
-1+0+C=4\implies C=5
\\\\\\
thus\qquad sin(\theta)-cos(\theta)+5=f'(\theta)\\\\
-----------------------------\\\\
[/tex]
[tex]\bf \displaystyle \int [sin(\theta)-cos(\theta)+5]d\theta\implies -cos(\theta)-sin(\theta)+5\theta+C=\underline{f(\theta)} \\\\\\ \textit{now, we know that \underline{f(0)=3}}\implies -cos(0)-sin(0)+5(0)+C=\underline{3} \\\\\\ -1-0+0+C=3\implies C=4 \\\\\\ thus\qquad -cos(\theta)-sin(\theta)+5\theta+4=f(\theta)[/tex]
[tex]\bf \displaystyle \int [sin(\theta)-cos(\theta)+5]d\theta\implies -cos(\theta)-sin(\theta)+5\theta+C=\underline{f(\theta)} \\\\\\ \textit{now, we know that \underline{f(0)=3}}\implies -cos(0)-sin(0)+5(0)+C=\underline{3} \\\\\\ -1-0+0+C=3\implies C=4 \\\\\\ thus\qquad -cos(\theta)-sin(\theta)+5\theta+4=f(\theta)[/tex]